OP0240 Signal Transducer and Activator of Transcription 3 Regulates Fibroblast Activation as A Downstream Mediator of Transforming Growth Factor-Beta. (10th June 2014) - Šumová, B.; Zerr, K.P.; Dees, C.; Zerr, P.; Distler, O.; Schett, G.; Senolt, L.; Distler, J.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease characterized by uncontrolled activation of fibroblasts with increased deposition of extracellular matrix. Persistent activation of TGFβ signalling is thought to play a key-role for the aberrant activation of fibroblasts in SSc. Signal transducer and activator of transcription 3 (STAT3) is transmitting signals from growth factor receptors at the plasma membrane receptors to nucleus. Objectives: The aim of this study was to evaluate the role of STAT3 in TGFβ induced fibroblast activation and to analyze the potential of STAT3 inhibition as a novel anti-fibrotic approach. Methods: The activation of STAT3 was analyzed by IF staining and by WB for pSTAT3. Selective inhibitors of JAK2 and STAT3 and knockout strategies were used to interfere with JAK2 and STAT3 signaling in vitro and in vivo . The anti-fibrotic potential of STAT3 inactivation by inducible fibroblast-specific knockout as well as with the small molecule inhibitor S3I-201 was evaluated in two mouse models of SSc: bleomycin-induced fibrosis and fibrosis induced by overexpression of a constitutively active TGFβ receptor type I (TBR). Results: Increased activation of STAT3 signaling was observed in SSc fibroblasts as well as in murine models of SSc. Stimulation with TGFβ induced phosphorylation of STAT3 and its nuclear accumulation in cultured fibroblasts. Inhibition of JAK2 by selective inhibitor TG101209 abrogated the TGFβ induced STAT3 activation and its nuclear accumulation, demonstrating TGFβ mediated STAT3 phosphorylation in a JAK2 dependent manner. Inactivation of STAT3 with the selective STAT3 inhibitor S3I-201 reduced the TGFβ induced activation of human fibroblasts with reduced mRNA levels of c ol1a1 and c ol1a2, decreased release of collagen protein (-56%, p=0.05) and impaired myofibroblast differentiation. Comparable results were observed when STAT3 was genetically inactivated in murine fibroblasts. In the model of bleomycin-induced skin fibrosis, fibroblast-specific knockout of STAT3 decreased hydroxyproline (HP) content by 39% (p<0.05). Potent anti-fibrotic effects were also observed in TBR induced fibrosis with HP content reduced by 47% (p<0.05). Moreover, treatment with the selective STAT3 inhibitor S3I-201 also effectively ameliorated bleomycin- and TBR-induced skin fibrosis at well tolerated doses (HP by 51% and by 60%; p<0.05). All models also showed significant decreases in dermal thickening and myofibroblast counts. Conclusions: Our study identifies STAT3 as a key-regulator of fibroblast activation and provides first prove that STAT3 is a novel intracellular mediator of the TGFβ signaling. We showed that the inhibition of STAT3 prevents fibroblast activation and exerts potent anti-fibrotic effect in preclinical models of SSc. These findings may have direct translational implications given that STAT3 inhibitors are currently in late clinical development. Acknowledgements: EULAR Health Professionals Educational Visit Grant Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2911